Development of Protected Underwater Landscapes Network’s in the Black and Azov Seas - Natalia Mitina; Katerina Chuprina (Emerging Issues in Environment, Geography and Earth Science Vol. 5, 2023)
This chapter concerned with the development of a comprehensive methodology to establish a MPAs (marine protected areas) network in the Black Sea and Azov Sea region. The Russian geographical science school has made significant progress in the development of methods of complex geographical studies of underwater landscapes and their classifications. The MPAs network is a sophisticated system of landscape zoning and mapping, defining their sustainability, variability, and geo-ecological state, and taking into consideration an assessment of the undersea landscape’s degradation over the past century. These claims are supported by scientific evidence. According to our classification, geographical zoning of the Azov-Black Sea basin—the MBNCs zoning map was created with scale of 1:1,250,000. Based on the developed classification and map of the Black and Azov Seas MBNCs with different hierarchical levels of the physiographic zoning, following methodology could be suggested for the development of an ecological network for MPAs. According to the ecosystem approch proposed by MPAs, a map was created. In the Azov-Black Sea physiographic country example of degraded MBNCs requiring urgent conservation measures are Zernov Phyllophora Field, oyster beds; MBNCs involved mussels biocenoses (Mytilus galloprovincialis), MBNCs, employed biocenoses eelgrass (Zostera noutii); MBNCs Mediterranean eel habitats (Conger conger), MBNCs of species listed in the Red Book, and estuary zone Kuban river Kuban to restore populations of commercial fish species, the MBNC, commonly used types of sturgeon for feeding, wintering, breeding, and transit. This study showed that the scientific basis for the justification of placing a network of MPA is a complex project including landscape zoning and mapping, confirmed by the analysis of the main components of the MBNCs indicators that determine their variability, stability, and geo-ecological condition.